VARIASI FONOLOGIS BAHASA INGGRIS ORANG KULIT HITAM AMERIKA DALAM LAGU-LAGU ALICIA KEYS - HARINI, METHUSALA MELANIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled Phonological Variation of Black American English in the Songs of Alicia Keys, and focuses on Alicia Keys’s fifth album, ‘The Diary of Alicia Keys’. Black American English is a unique English varieties that growing in the black Americans society, it have a different grammar and pronounce. This research is conducted by using a descriptive method. In collecting data, the first thing that the writer do is taking the lyrics from internet. Then, identifies those words that contains this variation. In analyzing data, the writer uses the theory of Rickford (1999) about phonological features of African American Vernacular English. The result of this research shows that there are some variations of African American Vernacular English in the songs of Alicia Keys, especially in the album ‘The Diary of Alicia Keys’. Such as: Reduction of word final consonants clusters, especially those ending in t and the –ed suffix pronounced as /t/, Deletion of word-final single consonant, Realization of final ng /ŋ/ as n /n/, Realization of voiceless th /θ/ as t, Realization of voiced /ð/ as d, Deletion or vocalization of l after a vowel, Deletion or vocalization of r after a vowel, Deletion of initial d and g in certain tense-aspect auxiliaries, Deletion of unstressed initial, Monophthongal pronunciation of ay, and ey, Most of the songs that sings by a black people have a different variation because their daily activities. The writer hopes that this study would give more knowledge to the readers in understanding the phonological variations of the Black American English, in the Faculty of Humanity, Sam Ratulangi University, Manado. Keywords: The Phonological Variations, Black American English/African American Vernacular English